Levels of anxiety, coping strategies of fathers, and their attitude towards having a child with mental illness - Paala, Rasel Suzzette R
This is a descriptive study which sought to determine the following: (1) the level of anxiety, (2) the coping strategies, and (3) the attitude of these fathers towards having a child with mental illness. Twelve fathers from Molo City were selected as respondents in this study. Questionnaires were utilized to study the variables under investigation. The findings showed that fathers have a moderate level of anxiety and they cope with the condition of their child through an emotion-focused strategy. Furthermore, these fathers have learned to accept their child, thus, having a positive attitude towards their child having a mental illness.